2015
DOI: 10.1111/codi.13017
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional high‐resolution anorectal manometry: does it allow automated analysis of sphincter defects?

Abstract: Our study developed a method based on 3D-HRAM to automatically diagnose sphincter defects, allowing a systematic and comprehensive analysis of the test recordings. Compared with EUS, the 3D-HRAM image analysis procedure revealed poor sensitivity and specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Two patients (5%) had a regional MRP < 10 mmHg in the FTA [ 15 , 16 ], 6 (15%) patients had regional MRP < 25 mmHg [ 17 ] and 21 (53%) patients had a regional MRP ≤ 50 mmHg.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Two patients (5%) had a regional MRP < 10 mmHg in the FTA [ 15 , 16 ], 6 (15%) patients had regional MRP < 25 mmHg [ 17 ] and 21 (53%) patients had a regional MRP ≤ 50 mmHg.…”
Section: Resultsmentioning
confidence: 99%
“…These findings could be used to tailor surgical therapy. This concept is indirectly supported by the studies by Vitton et al, who found only a moderate correlation between the detection of sphincter defects with 3D-HRAM and EUS [ 16 , 17 ]. A recent study confirmed these results [ 18 ].…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…1). The technique is more intuitive and reproducible, and has better inter-observer agreement when compared to the conventional procedure (8,9). It is also easier to perform, as the whole study may be carried out without catheter mobilization, and more accurate regarding the relationship between balloon distension and motor response.…”
Section: Fig 1 Resting Anal Canal Pressure and Maximum Voluntary Comentioning
confidence: 99%